2015
DOI: 10.1016/j.cell.2015.04.043
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Insights into the Dynamic Process of β 2 -Adrenergic Receptor Signaling

Abstract: SUMMARY G protein-coupled receptors (GPCRs) transduce signals from the extracellular environment to intracellular proteins. To gain structural insight into the regulation of receptor cytoplasmic conformations by extracellular ligands during signaling, we examine the structural dynamics of the cytoplasmic domain of the β2-adrenergic receptor (β2AR) using 19F-fluorine NMR and double electron-electron resonance spectroscopy. These studies show that unliganded and inverse-agonist-bound β2AR exists predominantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

50
548
3
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(606 citation statements)
references
References 39 publications
50
548
3
5
Order By: Relevance
“…Furthermore, this places our work in agreement with the transition state theories (recent works: refs. [5][6][7][8]. Physiochemical properties of the ligand-other than vibrational quanta-are likely involved in the activation of both ORs-as suggested for Drosophila receptors by Saberi and Seyed-allaei (91)-and GPCRs in general.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this places our work in agreement with the transition state theories (recent works: refs. [5][6][7][8]. Physiochemical properties of the ligand-other than vibrational quanta-are likely involved in the activation of both ORs-as suggested for Drosophila receptors by Saberi and Seyed-allaei (91)-and GPCRs in general.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, high resolution cryo-EM on asymmetric and relatively small membrane proteins (<200 kDa) remains challenging due to the low signal-to-noise ratio that hampers the accuracy of angular determination for 3D reconstructions. This problem is compounded by the intrinsically dynamic character of the 7TM bundle 14, 15 and the relative instability of GPCR complexes, such as with G proteins 16 or arrestins 17 , often resulting in conformational variability or even dissociation during cryo-EM specimen preparation. Notwithstanding these challenges, cryo-EM visualization for GPCR complexes holds tremendous potential for uncovering the various molecular mechanisms involved in signal transduction and regulation of GPCRs and their effector proteins.…”
mentioning
confidence: 99%
“…Interestingly, the dynamic equilibrium of receptors remains heterogeneous even in the presence of saturating concentrations of full agonists and always contains a fraction of receptors in inactive states (19,(21)(22)(23). In fact, agonists alone are not sufficient to stabilize the fully active receptor state as seen in the crystal structures (19 -24).…”
mentioning
confidence: 99%
“…Recent biophysical studies on various receptors (Class A and Class C) have shown that GPCRs reside in a dynamic equilibrium of distinct receptor conformations comprising inactive and active receptor states (19 -22). These studies suggest a common mechanism for agonist efficacy: agonists shift the preexisting equilibrium of different receptor conformations toward more active states (21,22).…”
mentioning
confidence: 99%